A Comprehensive Analysis of the Views of Turkish Teachers on the Process of Intercultural Education. (1st March 2016) - Altun, Sertel
Abstract: This study aims to analyse views of 10 teachers at selected private and national high schools in Turkey regarding an international project to develop intercultural sensitivity. Throughout the project, seminars and workshops by academic experts were prepared for the teachers concerning; intercultural awareness, culture and education, student-centred learning methods, learning styles, multiple intelligence theory, empathy, and teacher research. With the guidance of academics, teachers developed lesson plans, applied these to their classes, presented the results at national and international meetings in which they met their colleagues from other countries and wrote articles about the process. While teachers were anxious about working with people from different countries and applying new methods at first, they later realized that achieved fruitful results. Moreover, they stated that intercultural awareness should be incorporated into all classes. They emphasized, however, that to be successful in such projects, teachers need fluency in English and a willingness to try new methods.